Historiografia da inserção do Brasil no regime internacional de acumulação nas eras FHC e Lula: do regional ao multilateral - Tanaka, Juliana Emy Carvalho [UNESP] (2014)
This thesis starts from the premiss a greater universalism of the Brazilian participation in the international regime in the Nova República and maintains that from 1995 to 2010 the Brazilian international politics, while maintaining its goal of development and growth of the country, changed his manner of engaging the autonomy the integration (terms of President Fernando Henrique Cardoso), to the position of autonomy through diversification (terms of President Luiz Inácio Lula da Silva), which reconfigured the foreign form of international insertion both in relation to other economic blocs, countries and institutions multilateral trade, as in the very productive internal structure in order in imports and exports of federal entities, and the development of the country